Proceedings of the 1979 ACM SIGMOD International Conference on Management of Data - SIGMOD '79 1979
DOI: 10.1145/582095.582097
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a relational data base management system

Abstract: The effect on the performance of data management systems of the use of extended storage devices, multiple processors and prefetching data blocks is analyzed with respect to one system, INGRES. Benchmark query streams, derived from user queries, were run on the INGRES system and their CPU usage and data reference patterns traced.The results show that the performance characteristics of two query types: data-intensive queries and overhead-intensive queries, are so different that it may be difficult to design a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Suppose queries types can be partitioned into overhead-intensite and data.intensite, under the condition that queries are overhead-intensive, the database will not be costeffective [Ha79]. It is further shown that data-intensive queries can be performed efficiently on database machines if the function performed on the data is a function the database machine provides [Ha82].…”
Section: Discussionmentioning
confidence: 99%
“…Suppose queries types can be partitioned into overhead-intensite and data.intensite, under the condition that queries are overhead-intensive, the database will not be costeffective [Ha79]. It is further shown that data-intensive queries can be performed efficiently on database machines if the function performed on the data is a function the database machine provides [Ha82].…”
Section: Discussionmentioning
confidence: 99%
“…Specializing the operating system functions leads to performance gains [HAWT79] , but even better performance is possible with the use of especially designed, custom-built In the IDM the data manipulation processor is called a "database accelerator" [BRIT80] ; in RAP it is a "cell processer" [SAD078] ; in DBC it is a "mass memory processor"…”
Section: Design Differences Of Database Machinesmentioning
confidence: 99%
“…A measured query in the INGRES data management system [HAWT79] that corresponds to queries in the business application performed data manipulation tasks 8.1% of the time.…”
Section: Business Applicationsmentioning
confidence: 99%
“…In addition, within both short transactions and long queries some of the pages are rereferenced, and are called locality sets (Chou and Dewitt, 1985). Viewed as a whole, the combination of transaction and query accesses generates all possib]Le access patterns (RodriguezRosell, 1976;Smith, 1978;Hawthorn and Stonebraker, 1979;Effelsberg and Loomis, 1984;Chou and Dewitt, 1985;Verkamo, 1985;Sacco and Schkolnick, 1986;Kearns and Defazio, 1989). Traditional buffer management policies (e.g., strict LRU policy that does not exploit the knowledge of access components such as sequential vs random accesses) may not provide good buffer hit probability (Smith, 1978;Effelsberg and Haerder, 1984;Teng and Gumaer, 1984;Chou and Dewitt, 1985;Sacco and Schkolnick, 1986;IBM, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, our characterization method first distinguishes three types of access patterns from a trace: (1) locality within a transaction, (2) random accesses by transactions, and (3) sequential accesses by long queries. The presence of these types of access behavior has been shown (Rodriguez-Rosell, 1976;Hawthorn and Stonebraker, 1979;Effelsberg and Loomis, 1984;Verkamo, 1985;Kearns and Defazio, 1989). Each access component can be accounted for separately, both in terms of buffer management as well as buffer hit prediction.…”
Section: Introductionmentioning
confidence: 99%